Hubungan Stres Kerja dengan Kualitas Tidur pada Perawat di Instalasi Rawat Inap Rumah Sakit Advent Manado - Permataratri Baso, Christanti; Artur Tennov Kawatu, Paul; Asrifuddin, Afnal (Pusat Riset dan Inovasi Nasional, 2025)
Sleep quality is a person's level of satisfaction and the extent to which a person gets enough sleep according to their needs. Poor sleep quality can trigger various problems at work, potentially leading to workplace accidents. Sleep disturbances and poor sleep quality are common among nurses, impacting their well-being and performance. High work stress and a challenging work environment are the main contributing factors to problems with sleep quality. Occupational stress has a significant role in affecting a person's sleep quality. High levels of stress can disrupt sleep patterns and decrease the quality of rest, thus impacting health. A YouGov survey in 2023, revealed that most adults in various countries, including Indonesia, still do not achieve ideal sleep hours. This study aims to analyze the relationship between work stress and sleep quality in nurses at the inpatient installation of Advent Hospital Manado. This study used analytic observational research with cross sectional study design. The population in this study were nurses working in the inpatient installation of Advent Hospital Manado with a total sample of 73 people with the sampling method used was total sampling. The results of the Spearman Rank test showed a significant relationship between work stress and sleep quality (p = 0.003 < α = 0.05), the correlation coefficient value (r) = 0.348 which is included in the weak category with a positive correlation direction (+). Based on the research conducted, it can be concluded that there is a significant relationship between work stress and sleep quality in nurses at the inpatient installation of Advent Hospital Manado.